Palestina e Iraq en el nuevo orden regional - Chahuán Chahuán, Eugenio (Revista de Estudios Árabes, 2014)
Professor Chahuán notes the destabilizing strategies that the U.S. practices to hold most of energy resources in the Middle East, while Israel continuously tries to neutralize any potential strengthening of neighboring countries, both aiming to transform the civilization and culture of the region, changing the political and social structures of these states into submissive and divided entities. In Palestine, the aim is to serve purely Zionist interests, while the objective in Iraq is to secure energy sources for America and the imposition of a new world order and globalization. Saudi Arabia could become the next target, as the actual fundamentalist regime has not been able to prevent becoming a center of anti-American activities. What is left of Palestine by Israel could be linked with Jordan and parts of Iraq as the “final solution” of that conflict and become the new ally instead of Saudi Arabia.